2012
DOI: 10.1089/ees.2010.0215
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics and By-Products of Naproxen in Aqueous Solutions by Gamma Irradiation

Abstract: This study focused on the degradation of the emerging contaminant naproxen in aqueous solutions by gamma irradiation. Influence of initial naproxen concentration, solution pH, various additives (CH 3 OH, H 2 O 2 , NO À 3 , and humic acid), and absorbed dose on naproxen degradation were investigated. At a naproxen concentration of 23.6 mg/L and an absorbed dose of 1.0 kGy, the extent of naproxen degradation was 98%. The degradation reaction of naproxen followed first-order like kinetics. Addition of 40 mg/L hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 17 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Its presence in different environments is becoming a serious problem because naproxen and its derivatives have adverse effects on biota, such as impairing the lipid peroxidation system of bivalves (Zheng et al 2012). MarcoUrrea et al (2010a) carried out almost complete biotransformation of naproxen by Trametes versicolor in 24 h. This drug was degraded at a concentration of 10 mg l -1 and 55 lg l -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Its presence in different environments is becoming a serious problem because naproxen and its derivatives have adverse effects on biota, such as impairing the lipid peroxidation system of bivalves (Zheng et al 2012). MarcoUrrea et al (2010a) carried out almost complete biotransformation of naproxen by Trametes versicolor in 24 h. This drug was degraded at a concentration of 10 mg l -1 and 55 lg l -1 .…”
Section: Introductionmentioning
confidence: 99%
“…The overwhelming concentration of naproxen is disadvantageous towards aquatic organisms because it may modify the function of ribonucleic acid (RNA). [16][17][18] It is important to recall that a ribonucleotide into the ribonucleic acid contains the pentose sugar (ribose), and one of the four nitrogenous bases such as adenine, cytosine, uracil, and guanine including a phosphate group. Indeed, a ribonucleic acid nitrogenous base can accept a proton from a naproxen molecule to produce a protonated ribonucleic acid and a conjugate base of naproxen (Scheme 7, reaction 1).…”
Section: Scheme 6 24 Naproxenmentioning
confidence: 99%
“…The carboxylate group of this conjugate base could act as a nucleophile towards a protonated ribonucleic acid (Scheme It has been reported that naproxen can be enzymatically decomposed in the aquatic environment through decarboxylation, which takes place on the carboxylic group, and the pyridoxal-5' -phosphate plays a role of a coenzyme in this organic reaction. [16][17][18] The reaction mechanism implies the extraction of a proton from the catalytic cysteine residue of the decarboxylase to produce the corresponding pyridoxal-5' -phosphate conjugate acid, and the cysteine residue conjugate base (Scheme 8, reaction 1), which facilitates the carboxylation of naproxen or the substrate. This step results in the loss a carbon dioxide as well as the regeneration of the enzyme and a carbanion compound intermediate formation (Scheme 8, reaction 2).…”
Section: Scheme 6 24 Naproxenmentioning
confidence: 99%
“…Soil contamination with heavy metals is now still a hotspot issue due to its effects on soil enzyme activity, microbial community, and its potential transfer characteristic to crops, which may affect crop yield and even human health through food web [1] . Some reports showed that heavy metals in some cereals, vegetables and fruits have exceeded or approached the critical value, which may affect food safety and pose threats to human health because of the biomagnification through the food chain [2][3][4][5] . However, most of the studies were limited to typically polluted areas of heavy metals such as mining areas, suburban areas, and farmlands of sewage irrigation [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%